The impact of increased school: Enrollment on economic growth in Tanzania - Holger Seebens; Peter Wobst (University of Bonn, Center for Development Research (ZEF), 2003)
Failure to accumulate human capital is one of the pressing problems of developing countries. Lacking human capital formation bears consequences on an economy wide level, since education contributes to labor productivity. We examine the impact of increased school enrollment with regard to economic growth and income inequality. A dynamic computable general equilibrium (DCGE) model applying a 2000 SAM for Tanzania is used to evaluate the quantitative long-term effects of increased school attendance on overall economic growth and welfare. In order to get an insight in how a potential skill upgrade would affect the economy, we simulate a government program that aims at increasing primary school enrollment. We find that an increase in human capital formation in the long run leads to higher economic growth rates and increases household incomes in a Pareto sense. The results show that the positive effects of enhanced human capital formation are rather moderate in terms of the distribution of the gains from economic growth and hence income inequality does not change substantially.
Keywords: 370; International Development; Labor and Human Capital; Allgemeinbildende Schule; Bildungsinvestition; Wirkungsanalyse; Wirtschaftswachstum; Simulation; Tansania; Verteilungswirkung